Pivotal in a pandemic: an interview with Ian Roberts, head of the WHO libraries (Journal of EAHIL, 2020)
This interview with the head of the World Health Organization’s Library Service took place in May 2020, at the height of the COVID-19 pandemic. The interview provides a snapshot of how COVID-19 has affected the library service in an organization which is at the centre of disseminating information and providing leadership during the pandemic. In the interview, various aspects of managing a library service during a pandemic are discussed, including: how the library copes with high demand; how they maintain a high-quality search and retrieval service; how they make use of partnerships; what are the emerging "lessons learned" for their service; and how they try to take care of their well-being.